Rancang Bangun Sistem Pengaturan Suhu Ruang Inkubator Bayi Berbasis Microcontroller AT89S51 - Sugito, Heri; Suryono, Suryono (BERKALA FISIKA, 2009)
A room temperature adjustment system for infant incubator has created using electrical sources phase controlling. This device used to create environment temperature which is normal and stabile, as in mother’s uterus. The main component of room temperature of infant incubator adjustment which uses electrical sources phase controlling is 100 watt fluorescent hot source, temperature sensor LM 35, ADC 0804, microcontroller AT89S51, DAC 0808, Op-Amp LM 741, Phase detector (IC TCA 785), optical isolator (optocoupler), SCR, Pulse transformator, Coding 74LS47 and seven segment display. The temperature sensor, LM 35, perform data acquisition to room temperature of infant incubator. Furthermore, it strengthened and transformed by ADC 0804 to be digital data and read by microcontroller AT89S51. Reading value compared to accepted value, reading difference use for remove phase activator IC TCA 785 through DAC 0808. IC TCA as phase adjuster through trigger SCR TIC 106, it used to obtain temperature variation in heater lamp. The result is setting poin value with reading value have been as according with extinct indicator of lamp at infant incubator room. Keywords: infant incubator, temperature, phase control, microcontroller.